An Improved Dynamic Password-based User Authentication Scheme for Hierarchical Wireless Sensor Networks - Turkanovic, M.; Holbl, M. (Elektronika ir Elektrotechnika, 2013)
User authentication is an important issue in wireless sensor networks (WSN). Das et al. recently proposed a dynamic password-based user authentication scheme for hierarchical wireless sensor networks (HWSN), which provides high security and a simple authentication approach. In this paper we present a flaw in Das et al.’s scheme that makes it infeasible for real-life implementation. Additionally, we demonstrate that Das et al.’s scheme has redundant elements. To overcome these imperfections we propose an enhanced user authentication scheme based on Das et al.’s, which is both efficient and secure. DOI: http://dx.doi.org/10.5755/j01.eee.19.6.2038